Closing the gap: bridging peripheral sensory nerve defects with a chitosan-based conduit: a randomized prospective clinical trial - Böcker, Arne Hendrik; Aman, Martin; Kneser, Ulrich; Harhaus-Wähner, Leila; Siemers, Frank; Stang, Felix (Journal of Personalized Medicine, 2022)
If tensionless nerve coaptation is not possible, bridging the resulting peripheral nerve defect with an autologous nerve graft is still the current gold standard. The concept of conduits as an alternative with different materials and architectures, such as autologous vein conduits or bioartificial nerve conduits, could not replace the nerve graft until today. Chitosan, as a relatively new biomaterial, has recently demonstrated exceptional biocompatibility and material stability with neural lineage cells. The purpose of this prospective randomized clinical experiment was to determine the efficacy of chitosan-based nerve conduits in regenerating sensory nerves in the hand. Forty-seven patients with peripheral nerve defects up to 26 mm distal to the carpal tunnel were randomized to receive either a chitosan conduit or an autologous nerve graft with the latter serving as the control group. Fifteen patients from the conduit group and seven patients from the control group were available for a 12-month follow-up examination. The primary outcome parameter was tactile gnosis measured with two-point discrimination. The secondary outcome parameters were Semmens Weinstein Monofilament Testing, self-assessed pain, and patient satisfaction. Significant improvement (in static two-point discrimination) was observed six months after trauma (10.7 ± 1.2 mm; < 0.05) for chitosan-based nerve conduits, but no further improvement was observed after 12 months of regeneration (10.9 ± 1.3 mm). After six months and twelve months, the autologous nerve graft demonstrated comparable results to the nerve conduit, with a static two-point discrimination of 11.0 ± 2.0 mm and 7.9 ± 1.1 mm. Semmes Weinstein Filament Testing in the nerve conduit group showed a continuous improvement over the regeneration period by reaching from 3.1 ± 0.3 after three months up to 3.7 ± 0.4 after twelve months. Autologous nerve grafts presented similar results: 3.3 ± 0.4 after three months and 3.7 ± 0.5 after twelve months. Patient satisfaction and self-reported pain levels were similar between the chitosan nerve conduit and nerve graft groups. One patient required revision surgery due to complications associated with the chitosan nerve tube. Chitosan-based nerve conduits are safe and suitable for bridging nerve lesions up to 26 mm in the hand. Tactile gnosis improved significantly during the early regeneration period, and functional outcomes were similar to those obtained with an autologous nerve graft. Thus, chitosan appears to be a sufficient substitute for autologous nerve grafts in the treatment of small nerve defects in the hand.
"This article belongs to the special issue 'Diagnosis and treatment in peripheral nerve surgery'" (Landingpage)